Decreasing Total Medication Exposure and Length of Stay While Completing Withdrawal for Neonatal Abstinence Syndrome during the Neonatal Hospital Stay - Devlin, Lori A.; Lau, Timothy; Radmacher, Paula G. (Frontiers in Pediatrics, 2017)
Introduction: Neonatal Abstinence Syndrome (NAS) is a rapidly growing public health concern that has considerably increased healthcare utilization and healthcare costs. In an effort to curtail costs attempts have been made to complete withdrawal as an outpatient. Outpatient therapy has been shown to prolong exposure to medications which may negatively impact neurodevelopmental and behavioral outcomes. We hypothesized that the implementation of a modified NAS protocol would decrease total drug exposure and length of stay while allowing for complete acute drug withdrawal during the neonatal hospital stay. Methods: Data were derived retrospectively from medical records of term (> 37 0/7) infants with NAS who were treated with pharmacologic therapy in the University of Louisville Hospital NICU from 2005 to 2015. The pharmacologic protocol (SP1) for infants treated between 2005 and March 2014 (n= 146) dosed oral morphine every 4 hours and utilized phenobarbital as adjuvant therapy. Protocol 2 (SP2) initiated after March 2014 (n= 44) dosed morphine every 3 hours and used clonidine as adjuvant therapy. Charts were reviewed for demographic information and maternal drug history. Maternal and infant toxicology screens were recorded. The length of morphine therapy and need for adjuvant drug therapy were noted. Length of stay was derived from admission and discharge dates. Results: The length of morphine therapy was decreased by 8.5 days from 35 to 26.5 days (95% CI 4.5 to 12 days) for infants treated with SP2 vs. SP1 (p< 0.001). The need for adjuvant pharmacologic therapy was decreased by 24% in patients treated with SP2 vs. SP1 (p=0.004). The length of stay was decreased by 9 days from 42 to 33 days (95% CI 5.1 to 13 days) for infants treated with SP2 vs. SP1 (p< 0.001). The decreased length of stay resulted in an average reduction of hospital charges by $27,090 per patient in adjusted 2015 US Dollars. Conclusions: The present study demonstrates that total drug exposure and length of stay can be reduced while successfully completing acute withdrawal during the neonatal hospital stay.